Biological parameters of Amblyomma coelebs Neumann, 1906 (Acari: Ixodidae) under experimental conditions - Aguirre,André de Abreu Rangel (2018)
Abstract One generation of Amblyomma coelebs life cycle under experimental conditions was evaluated. Ten tick pairs were allowed to feed on rabbits under laboratory conditions (LC), resulting six engorged females with a mean weight of 1,403.9 mg. Two females were maintained in a forest reserve under natural conditions (NC), and four were maintained in incubators (LC). The engorgement period lasted 10.33 days. Pre-oviposition periods were 10.75 (NC) and 22 days (LC). The mean egg-mass weight was 514.76 mg, and the blood meal conversion index was 36.67% (LC). Incubation period under NC and LC were 91 and 56.33 days and hatching rates were 50% and 28.33%, respectively. Larval engorgement period ranged from 4 to 10 days, with average weight of 1.1 mg. Engorged larvae were incubated under NC and LC, with a premolt period of 27 to 36 days and molting rate of 7.1% and 28.7%, respectively. Nymphal engorgement period ranged from 5 to 7 days, with a mean weight of 18.8 mg and a recovery rate of 54.54%. In LC, the ecdysis mean period was 24.5 days, and molting rate was 44.44%, resulting in 24 adult A. coelebs. Our results show a life cycle of 187.45 (NC) and 149 (LC) days.